2022
DOI: 10.3389/fpsyt.2022.1046804
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of the gut microbiota in the manifestations of drug use disorders

Abstract: Drug use disorders (DUDs) not only cause serious harm to users but also cause huge economic, security, and public health burdens to families and society. Recently, several studies have shown that gut microbiota (GM) can affect the central nervous system and brain functions. In this review, we focus on the potential role of the GM in the different stages of DUDs. First, the GM may induce individuals to seek novel substances. Second, the gut microbiota is involved in the decomposition and absorption of drugs. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Specifically, recent findings have revealed that individuals with substance addiction exhibit altered GM composition and diversity, which affect stress response, depression, immune modulation, and the synthesis and metabolism of neurotransmitters, particularly serotonin and dopamine. In this scenario, since many drugs of abuse are well known to alter gastrointestinal functionality through the alteration of GM structure [5], the relationship between GM dysbiosis and SUD has been widely documented in both rodents and humans. For instance, increased permeability of the intestinal barrier and altered gut-brain communication are noted in alcohol use disorder (AUD).…”
Section: Microbiota Dysbiosis and Sudmentioning
confidence: 99%
“…Specifically, recent findings have revealed that individuals with substance addiction exhibit altered GM composition and diversity, which affect stress response, depression, immune modulation, and the synthesis and metabolism of neurotransmitters, particularly serotonin and dopamine. In this scenario, since many drugs of abuse are well known to alter gastrointestinal functionality through the alteration of GM structure [5], the relationship between GM dysbiosis and SUD has been widely documented in both rodents and humans. For instance, increased permeability of the intestinal barrier and altered gut-brain communication are noted in alcohol use disorder (AUD).…”
Section: Microbiota Dysbiosis and Sudmentioning
confidence: 99%